Strategic Planning Development for Business Activities at Al-Fitrah Pesantren, Surabaya (Journal Evaluation in Education (JEE), 2025)
Purpose of the study: This study aimed to develop a strategic entrepreneurship plan for students at Al-Fithrah Islamic Boarding School, as an effort to strengthen entrepreneurship education within the pesantren ecosystem by aligning the institution’s vision and mission with actionable and sustainable strategies for student entrepreneurial development.Methodology: Employing a developmental research approach based on the Borg and Gall model, the study followed 10 systematic stages from research and information gathering through product development, field testing, revision, and dissemination. Data were collected through expert validation questionnaires and evaluation instruments completed by caregivers, ustadz, and students, ensuring they met standards of feasibility, practicality, and effectiveness.Main Findings: The plan’s feasibility is supported by strong alignment with institutional values, comprehensive internal and external environmental analyses, the formulation of measurable objectives, and coherence between strategies and operational action plans. Practicality was demonstrated through the development and use of a strategic planning guidebook that accommodated diverse educational backgrounds and teaching experiences, helping stakeholders address implementation challenges. The plan proved effective through the creation of a clear strategy map and structured business planning pathway, enabling students to systematically build entrepreneurship competencies across the introduction, reinforcement, and expansion stages.Novelty/Originality of this study: The formulation of a pesantren-based strategic entrepreneurship planning model that integrates religious learning, character education, and entrepreneurial practice, an approach rarely addressed in previous studies. This integration provides a transformative model for Islamic boarding schools seeking to cultivate spiritually grounded yet economically empowered young entrepreneurs.
Keywords: Entrepreneurship; Islamic Boarding School; Strategic Plan